Exploring Students’ and Teachers’ Perceptions of Linguistic Immersion in Enhancing Arabic Speaking Proficiency as a Second Language - Anwar; Assapari, Muhammad Mugni; Aziz, Abdul (Shaut al Arabiyyah, 2025)
This investigation examines learner and instructor perspectives on Arabic linguistic immersion at Ponpes Al Kautsar Al Gontory, Lombok-NTB, assessing its effectiveness in developing oral proficiency. Utilizing a qualitative methodology, the research employs in-depth interviews to gather comprehensive experiential data from participants. The collected findings illustrate immersion-based language instruction's transformative potential and implementation challenges. Analysis indicates that immersive approaches substantially enhance learners' communicative confidence, with overwhelming participant consensus regarding their beneficial effects on Arabic acquisition. The result of this study Teachers overwhelmingly (85-100%) support Arabic immersion, noting improved student confidence and skills. Some (14.3%) need clearer immersion concepts.100% of students support Arabic immersion, with 92.3% feeling comfortable. While 76.9% faced initial adaptation challenges, all reported improved confidence and fluency. The results confirm immersion's effectiveness but highlight the need for structured support and gradual implementation. Furthermore, the outcomes underscore critical considerations for immersion initiatives, advocating for structured curricular designs incorporating adaptive scaffolding, individualized methodologies, and culturally appropriate materials in Islamic boarding school environments. The research yields significant conceptual and applied advancements in Arabic pedagogy.